Racial and Cultural Identity in Chinese Peranakan Literature: Cerita Satu Ibu Tiri yang Pinter Ajar Anak - Dewojati, Cahyaningrum; Ekaristi, Lidwina Putu Gratia (Metta : Jurnal Ilmu Multidisiplin, 2025)
The diversity of Indonesia's identity and culture as a heterogeneous country cannot be separated from the character of the Indonesian nation, which has been inclusive from the start. The Chinese, Arab, Indian, and European diaspora during the colonial period made Indonesia's big cities a melting pot where various ethnicities, races, and cultures met. Authors, including Peranakan Chinese, were generally educated people. Their writing reflects the dialectics and dynamics between cultures, both from the Peranakan Chinese community and the native people, Europeans, Arabs, or other ethnic groups that form the background of the stories. This is also represented in one of the Chinese Peranakan literary works, Cerita Satu Ibu Tiri yang Pinter Ajar Anak (1913), which will be used as a material object in this research. The drama text describes the dynamics of community life, cultural friction, social conflict, and issues of ethnicity/race during the Dutch colonial period. This research aims to narrate the dynamics of multiethnic cultures that coexisted in Indonesia during the colonial period in literary works. Qualitative descriptive methods are used to explain the data found. They will describe the identity of multiethnic communities who maintained their respective identities, traditions, and cultures during the Dutch colonial period.